2020
DOI: 10.1145/3396044
|View full text |Cite
|
Sign up to set email alerts
|

TimeToFocus

Abstract: Many computer tasks involve looking up information from different sources. Such interruptions to a task can be disruptive. In this paper, we investigate whether giving people feedback on how long they are away from their task influences their self-interruption behaviour. We conducted a contextual inquiry on self-interruption behaviour in an office workplace. Participants were observed to postpone physical interruptions until a convenient moment in the task if they were expected to take time. In contrast, obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Spatialization within VR seems to reduce mental workload only if tasks require such cognitively-related resources (Filho et al, 2018(Filho et al, , 2020Wismer et al, 2018;Armougum et al, 2019;Bernard et al, 2019;Broucke and Deligiannis, 2019;Baceviciute et al, 2021) Multitasking (Ahmad et al, 2021), especially interruptions (Cheng et al, 2020;Mcmullan et al, 2021) impacts negatively performance due to higher mental workload. Incongruent (with the primary task) emails (Addas and Pinsonneault, 2018), notifications (Tan et al, 2020) distract users Consider reducing tasks' difficulty by: Reducing multitasking (fewer notifications, no incongruent emails during a given task) and allow users to predict multitasking (Ewolds et al, 2021) Testing interactions and interfaces to make sure they do not require unnecessary working memory solicitations by using questionnaires such as the NASA-TLX (Hart and Staveland, 1988;Hart, 2006;Grier, 2015;Hertzum, 2021) can be used only using spatialized information and interaction if the tasks require it Provide virtual assistant, visual cues, and feedback on how users are fulfilling tasks and their mental workload to help them focus on the primary task (Weng et al, 2017;Borghouts et al, 2020) Consider adapting interactions and interfaces based on the user's characteristics or preferences (Chen et al, 2019) In collaboration requiring object localization by speaking, avoid the spatial configurations diagonally in front and behind speakers (Milleville-Pennel et al, 2020) Allow users to train enough at tasks, interactions, and interfaces See also S_6…”
Section: Task Difficultymentioning
confidence: 99%
“…Spatialization within VR seems to reduce mental workload only if tasks require such cognitively-related resources (Filho et al, 2018(Filho et al, , 2020Wismer et al, 2018;Armougum et al, 2019;Bernard et al, 2019;Broucke and Deligiannis, 2019;Baceviciute et al, 2021) Multitasking (Ahmad et al, 2021), especially interruptions (Cheng et al, 2020;Mcmullan et al, 2021) impacts negatively performance due to higher mental workload. Incongruent (with the primary task) emails (Addas and Pinsonneault, 2018), notifications (Tan et al, 2020) distract users Consider reducing tasks' difficulty by: Reducing multitasking (fewer notifications, no incongruent emails during a given task) and allow users to predict multitasking (Ewolds et al, 2021) Testing interactions and interfaces to make sure they do not require unnecessary working memory solicitations by using questionnaires such as the NASA-TLX (Hart and Staveland, 1988;Hart, 2006;Grier, 2015;Hertzum, 2021) can be used only using spatialized information and interaction if the tasks require it Provide virtual assistant, visual cues, and feedback on how users are fulfilling tasks and their mental workload to help them focus on the primary task (Weng et al, 2017;Borghouts et al, 2020) Consider adapting interactions and interfaces based on the user's characteristics or preferences (Chen et al, 2019) In collaboration requiring object localization by speaking, avoid the spatial configurations diagonally in front and behind speakers (Milleville-Pennel et al, 2020) Allow users to train enough at tasks, interactions, and interfaces See also S_6…”
Section: Task Difficultymentioning
confidence: 99%
“…Most of the current research on interruptions has focused on the effects of interruptions on behavioral performance, and several characteristics modulate interruptions (Borghouts et al, 2020; Lee & Duffy, 2015; Monk et al, 2008; Pankok et al, 2017). Few researchers have examined relevant cognitive processes (Werner et al, 2015), and few studies have investigated the neural mechanisms in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work found that feedback is especially effective if it promotes self-assessment 25 . Compared to existing research 15 , our findings are based on a much larger sample and evaluate not only productivity but gain more in-depth insights into individual self-regulation by experience sampling dialogs present in the software. Beyond performance-related gains, we could show that our application’s feedback promotes self-assessment by reminding users of their self-set goals, continuously supporting self-evaluation, and monitoring of their progress towards these goals.…”
Section: Discussionmentioning
confidence: 97%
“…While the authors found such reminders to reduce task-switching frequency, these prompts do not provide feedback on resource investment related to reaching respective task goals. Building on these insights, the browser-based tool TimeToFocus 15 provides feedback on the time spent interrupted on average during previously interrupted periods upon the start of an interruption. However, this immediate feedback does not refer to actual behavior but provides a summative reference to past behavior.…”
Section: Introductionmentioning
confidence: 99%